Effect of Visceral Fat on Blood Pressure Levels: Pengaruh Lemak Visceral pada Tingkat Tekanan Darah - Hasan, Mhfoudh Falih; Mahdi, Weam Saleh; Hadi , Firas; thanon, Kawther saleh; Atiyah, Maher Abdulameer; Mutashar, Mohammed Kadhim (Indonesian Journal on Health Science and Medicine, 2025)
Background: Visceral fat is a key health indicator due to its physiological link to vital body functions, particularly blood pressure regulation. Elevated visceral fat has been associated with an increased risk of cardiovascular diseases and metabolic disorders. Specific Background: High blood pressure, a chronic condition characterized by elevated arterial pressure, is influenced by various physiological factors, including body composition. The excessive accumulation of visceral fat can contribute to hypertension by impacting cardiovascular and metabolic functions. Knowledge Gap: Despite existing studies on obesity and hypertension, limited research has explored the direct correlation between visceral fat levels and blood pressure among university students in Iraq. Aims: This study aims to assess visceral fat levels and blood pressure among students at the Open Educational College – Basra Center and examine the relationship between these two variables. Results: Among 85 participants (42% male, 58% female, mean age 40.14 years), 55% had abnormal visceral fat levels, and 52% exhibited elevated blood pressure. Chi-square analysis revealed a significant relationship (X² = 8.125, p = 0.028) between visceral fat and hypertension, indicating that individuals with higher visceral fat percentages were more likely to have elevated blood pressure. Novelty: This study provides empirical evidence linking visceral fat accumulation to increased blood pressure in an understudied population, reinforcing the importance of visceral fat as a predictive factor for hypertension. Implications: The findings highlight the necessity for targeted health interventions, including lifestyle modifications and public health strategies, to mitigate the risks associated with excessive visceral fat accumulation and hypertension. Future research should further investigate underlying mechanisms and preventive measures tailored to at-risk populations. Highlights: Visceral fat impacts blood pressure, influencing cardiovascular health. Higher visceral fat correlates with increased blood pressure levels. Managing visceral fat may help regulate blood pressure and prevent complications. Keywords: Visceral fat, blood pressure, obesity, cardiovascular health, hypertension.